2019
DOI: 10.32448/entupdates.570136
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the factors affecting the success of vestibular rehabilitation therapy in patients with idiopathic unilateral vestibular hypofunction and idiopathic bilateral vestibular hypofunction

Abstract: Objective: The aim of this study was to determine the factors affecting the success of vestibular rehabilitation therapy (VRT) in patients with idiopathic unilateral vestibular hypofunction (UVH) and idiopathic bilateral vestibular hypofunction (BVH).Methods: 30 patients with idiopathic UVH and 30 patients with idiopathic BVH were included in this prospective study. Visual analog scale (VAS) was used to evaluate the severity of the patients' complaints of dizziness. The duration of the complaint of dizziness w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Two studies (Ertugrul and Emre Soylemez,173 level II; Itani et al,179 level III) did not find an effect of age on rehabilitation outcomes for individuals with various peripheral vestibular disorders. Lorin et al213 (level IV) reported that increasing age was not associated with functional outcomes after VPT.…”
Section: Update and Revision Of Guidelinesmentioning
confidence: 92%
See 1 more Smart Citation
“…Two studies (Ertugrul and Emre Soylemez,173 level II; Itani et al,179 level III) did not find an effect of age on rehabilitation outcomes for individuals with various peripheral vestibular disorders. Lorin et al213 (level IV) reported that increasing age was not associated with functional outcomes after VPT.…”
Section: Update and Revision Of Guidelinesmentioning
confidence: 92%
“…Three studies evaluated the effect of gender on the efficacy of VPT, and none demonstrated a significant effect of gender on recovery. One level III study found no effect of gender on multiple vestibular rehabilitation outcomes in individuals with BVH 112 and 2 other level III studies found no effect of gender on DGI (Itani et al 179 ) or DHI (Ertugrul and Emre Soylemez 173 ) scores in individuals with various peripheral vestibular disorders.…”
Section: Gendermentioning
confidence: 98%